A Juridical Analysis of the Title Revocation of Senegal's 2025 AFCON: A Review of Walk-out Sanctions under CAF Regulations - Marselius Nataniel Situmeang; Vincentius Hansel Darmawan; Ahmad Dyfan Nadhif Islamy (Indonesian Journal of Sports Law, 2025)
This study analyzes the juridical conflict surrounding the revocation of the Senegal National Team’s 2025 Africa Cup of Nations (AFCON) championship title by the Confédération Africaine de Football (CAF). The research focuses on the "analytical gap" between the enforcement of strict disciplinary sanctions for a match "walk-out" and the fundamental principle of legal certainty. Using a normative legal research method with a doctrinal and conceptual approach, this article examines the CAF Disciplinary Code (Articles 82–84) and the FIFA Statutes within the framework of lex sportiva. The results indicate that while Senegal’s mid-match protest formally violated competition integrity rules, the administrative decision to annul a 1-0 on-field victory and convert it to a 3-0 loss sixty days after the final whistle severely undermines the "finality of the referee’s decision" (Law 5.2 LOTG) and the stability of sporting results. Furthermore, because the team eventually returned to complete the match, the retroactive title revocation is deemed a disproportionate punitive measure. The study concludes that there is an urgent need to reform international sports law to include clear "statutes of limitations" for administrative interventions to protect vested rights and ensure that the dignity of the game is not superseded by unpredictable, retroactive adjudication.